2015
DOI: 10.1515/ngoe-2015-0010
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Export-led Growth Hypothesis: The case of Croatia

Abstract: This paper examines the relationship between gross domestic product and exports of goods and services in Croatia between 1996 and 2012. The research results confirmed unidirectional Granger causality from the exports of goods and services to gross domestic product. Following the Engle-Granger approach to cointegration, long-term equilibrium as well as short-term correlation between the observed variables was identified. Exports of goods and services and gross domestic product (GDP) in Croatia move together. If… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The first group includes studies, whose findings are consistent with a unidirectional causal flow from exports to economic growth. These studies include, amongst other, studies such as Boame (1998) for the case of Ghana; El-Sakka and Al-Mutairi (2000) for Iraq, Morocco, Saudi Arabia and Syria; Fountas (2000) for Ireland; Awokuse (2003) for Canada; Shirazi and Manap (2005) for Pakistan; Siliverstovs and Herzer (2006) for Chile; Jordaan and Eita (2007) for Namibia; Narayan et al (2007) for the case of Papua New Guinea in the short run and Fiji in the long run; Dash (2009) for India; Rangasamy (2009) for South Africa; Uddin et al (2010) for Bhutan; Ramona et al (2010) for Romania; Samad (2011) for Algeria; Saad (2012) for Lebanon; Tsaurai and Odhiambo (2012) for Zimbabwe; Dritsaki (2013) for Greece; Abdulkarim (2014) for Saudi Arabia; Bilas et al (2015) for Croatia; Ee (2016) for the case of selected sub-Saharan African (SSA) countries; Ali and Li (2018) for China and Pakistan; Ahmad et al (2018) for ASEAN5 economies; Dinç and Gökmen (2019) for the case of Brazil in the short run; Kalaitzi and Chamberlain (2020) for the case of the United Arab Emirates in the short run; Kim et al (2019) for Myanmar; Shakeel and Ahmed (2020) for a panel of five South Asian countries in the long run.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The first group includes studies, whose findings are consistent with a unidirectional causal flow from exports to economic growth. These studies include, amongst other, studies such as Boame (1998) for the case of Ghana; El-Sakka and Al-Mutairi (2000) for Iraq, Morocco, Saudi Arabia and Syria; Fountas (2000) for Ireland; Awokuse (2003) for Canada; Shirazi and Manap (2005) for Pakistan; Siliverstovs and Herzer (2006) for Chile; Jordaan and Eita (2007) for Namibia; Narayan et al (2007) for the case of Papua New Guinea in the short run and Fiji in the long run; Dash (2009) for India; Rangasamy (2009) for South Africa; Uddin et al (2010) for Bhutan; Ramona et al (2010) for Romania; Samad (2011) for Algeria; Saad (2012) for Lebanon; Tsaurai and Odhiambo (2012) for Zimbabwe; Dritsaki (2013) for Greece; Abdulkarim (2014) for Saudi Arabia; Bilas et al (2015) for Croatia; Ee (2016) for the case of selected sub-Saharan African (SSA) countries; Ali and Li (2018) for China and Pakistan; Ahmad et al (2018) for ASEAN5 economies; Dinç and Gökmen (2019) for the case of Brazil in the short run; Kalaitzi and Chamberlain (2020) for the case of the United Arab Emirates in the short run; Kim et al (2019) for Myanmar; Shakeel and Ahmed (2020) for a panel of five South Asian countries in the long run.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to application results, there is one-way causality from real export to real GDP. Bilas, Bosnjak and Franc (2015) tested the relationship between GDP and export with Granger causality test for Croatia. Test results showed that during the period 1996-2012, ELG strategy is accepted.…”
Section: Empirical Literaturementioning
confidence: 99%
“…We concentrated on the following industries: agriculture, forestry and fishing, mining and quarrying, manufacturing, and information and communication. The intention was to exclude services, especially tourism and transportation that significantly impact Croatian exports, according to the suggestion of separating exports of goods and services in the study by Bilas, Bošnjak, and Franc (2015). The Bisnode database has identified 25,423 companies from those industries that are involved in export activities, which makes up about 8% of all registered companies.…”
Section: Methodsmentioning
confidence: 99%